INTERNATIONAL PRINCIPLES FOR THE VALUATION OF GOODS FOR CUSTOMS PURPOSES - Zareta Rudneva (Вестник Северо-Кавказского федерального университета)
The article analyzes the international principles of customs valuation of goods. Failure to comply with the principles entails the illegality of the application of methods for determining the customs value, as well as its value, which determines the amount of customs duties and taxes payable for goods transported across the customs border. Despite the fact that the international principles of customs valuation are common and interrelated, the article defines the problems of their implementation by customs authorities and participants offoreign economic activity within the Eurasian economic Union.